Assessment of the Safety Climate at University Hospitals in the Slovak Republic from the Nurses’ Perspective - Kalankova D; Bartonickova D; Ziakova K; Gurkova E; Kurucova R (Acta Medica Martiniana, 2020)
Introduction: Safety climate consists of individual dimensions that might be assessed using specific instruments, e.g., the Hospital Survey on Patient Safety Culture (HSOPS). Establishing the safety climate in healthcare facilities leads to improvements in patient safety.